Landslide Science and Practice Volume 5: Complex Environment - Margottini, Claudio; Canuti, Paolo; Sassa, Kyoji (Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book contains peer-reviewed papers from the Second World Landslide Forum, organised by the International Consortium on Landslides (ICL), that took place in September 2011. The entire material from the conference has been split into seven volumes, this one is the fifth: Landslide Inventory and Susceptibility and Hazard Zoning, Early Warning, Instrumentation and Monitoring, Spatial Analysis and Modelling, Global Environmental Change, Complex Environment, Risk Assessment, Management and Mitigation, Social and Economic Impact and Policies.